Coupling effects of power substation equipment with multiple configurations. Issue 150 (November 2021) - Xie, Qiang; Wen, Jiayi; Liu, Weichen
Abstract: Power substation equipment with multiple configurations use metallic blades to switch to different service configurations. When subjected to earthquakes, a closed blade can produce great coupling effects between two interconnected pieces of the equipment, which substantially affect their dynamic properties and seismic responses. However, knowledge of the coupling effects and their production mechanism is currently insufficient. To investigate coupling effect characteristics, an ultra-high voltage (UHV) disconnect switch with different configurations was tested on a full-scale shaking table. Test results proved that the main blade was a weak connection, which leads inconsistent resonance among different pieces. Furthermore, phase traces of the blade confirm its coupling effects are produced by a nonlinear mechanism. Combined testing results and a numerical calculation were employed to quantitatively estimate the interaction forces raised by the blade. Based on a frequency-domain characteristic analysis, it was found that the nonlinearity was contributed by by the unsteady connection of the blade. Furthermore, this study proved that the blade connection cannot be modeled by a single linear element with any physical parameters. Highlights: Full-scale shaking table testing on large equipment with multiple configurations. Mass effect of the switchable blade varying with configurations of equipment. Closed blade showing weakly-constraint effects on interconnected pieces. Nonlinearity of the blade interactions produced by unsteady boundary condition.